Experimental acute pancreatitis induced by platelet activating factor in rabbits. - Emanuelli, G. (1989)
This study indicates that a single injection of platelet activating factor (PAF, 50-500 ng) into the superior pancreaticoduodenal artery of rabbits induces dose-dependent morphologic alterations of pancreatic tissue and increases serum amylase levels, both consistent with the development of an acute pancreatitis. The main histologic findings observed by light microscopy 24-72 hours after the injection of PAF were edema, polymorphonuclear neutrophil infiltration, cell vacuolization, and acinar cell necrosis. Fat cell necrosis was present in 30% of animals. By electron microscopy an increase of the number of zymogen granules in the apical region of acinar cells was observed 3 hours after PAF challenge. At 24-72 hours, many acinar cells showed vacuoles containing myelinlike figures, zymogen granules, and cellular debris. Pancreatic lesions developed in the area supplied by the artery injected with PAF and they were completely antagonized by the pretreatment of rabbits with CV 3988, a specific antagonist of PAF. In addition, the significant protective effect of atropine suggests a potential role for cholinergic mechanisms in the pancreatic alterations induced by PAF.